2012
DOI: 10.1001/archinternmed.2012.777
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacilli vs Antibiotics to Prevent Urinary Tract Infections

Abstract: In postmenopausal women with recurrent UTIs, L rhamnosus GR-1 and L reuteri RC-14 do not meet the noninferiority criteria in the prevention of UTIs when compared with trimethoprim-sulfamethoxazole. However, unlike trimethoprim-sulfamethoxazole, lactobacilli do not increase antibiotic resistance. TRIAL REGISTRATION isrctn.org Identifier: ISRCTN50717094.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(86 citation statements)
references
References 21 publications
2
74
1
1
Order By: Relevance
“…One limitation of our study is that although it tested resistance to a wide range of antibiotics, not all antibiotic recommendations in the guidelines were covered on a one-on-one basis and in some cases we had to use the prevalence of resistance to a similar antibiotic [30,31]. Also, since we excluded patients with current infections or risk factors for AMR (antibiotic use or hospitalisation in the past 3 months), the level of AMR might be an underestimation for the total population in the community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One limitation of our study is that although it tested resistance to a wide range of antibiotics, not all antibiotic recommendations in the guidelines were covered on a one-on-one basis and in some cases we had to use the prevalence of resistance to a similar antibiotic [30,31]. Also, since we excluded patients with current infections or risk factors for AMR (antibiotic use or hospitalisation in the past 3 months), the level of AMR might be an underestimation for the total population in the community.…”
Section: Discussionmentioning
confidence: 99%
“…since no clarithromycin resistance was tested we used data of azithromycin resistance (see Additional file 2: Table S2). Recent studies have shown that resistance to similar antibiotics can serve as a reliable indicator for the level of resistance to the original antibiotic [30,31]. …”
Section: Methodsmentioning
confidence: 99%
“…In randomised trials comparing continuous co-trimoxazole (480mg daily) with cranberry extract12 and lactobacillus,13 resistance to co-trimoxazole, trimethoprim and amoxicillin in faeces and urine (measured by testing antibacterial sensitivity in the laboratory) had increased after 1 month of antibacterial use (from around 21–28% to around 73–91% in one trial;12 and from around 20–40% to around 80–95% in the other) 13. After 12 months' prophylactic therapy, resistance rates for ciprofloxacin and norfloxacin in urinary Escherichia coli isolates had also increased.…”
Section: Preventing Recurrent Infectionsmentioning
confidence: 99%
“…A more recent double-blind, double-dummy randomised controlled trial in 252 postmenopausal women with recurrent UTIs compared 12 months' prophylaxis with either co-trimoxazole (480mg daily) or oral capsules containing Lactobacillus ( twice daily) 13. The trial included women with complicated UTIs.…”
Section: Preventing Recurrent Infectionsmentioning
confidence: 99%
“…Quinolone therapy during the prior 6 months increased the odds that a febrile UTI was caused by a quinolone-resistant organism 17.5 times in outpatients 7. Trimethoprim/sulfamethoxazole prophylaxis for 1 month in postmenopausal women increased resistant Escherichia coli in the stool from approximately 20% to 85% 8. Of interest, a recent study found that antibiotic treatment of asymptomatic bacteriuria in young women increased the risk of subsequent symptomatic UTI 3 times.…”
mentioning
confidence: 99%